Study on Resistance Loss of Fly Ash Slurry Multistage High-Pressure Grouting Pipeline Based on Fluent - Qiqing Wang; Linzhe Li; Huijie Wu; Kun Wang; Sixiang Wang (Geofluids)
In order to understand the resistance loss along the way during multistage high-pressure slurry transportation, the flow state of fly ash slurry in the pipeline was simulated by Fluent software in this paper, and the effects of pipe diameter D, pipe transportation flow rate Q, and fly ash mass concentration Cw on the resistance loss along the pipeline were studied. The fly ash slurry is a non-Newtonian Bingham fluid that moves in a turbulent state in a pipeline. When simulating the flow of fly ash slurry using Fluent software, the mesh type is a mixed mesh of hexahedron and wedge shapes, and the viscous model is selected as realizable k-ε Turbulence Model, with Enhanced-Wall Function (EWF) selected as the wall function, combined with a four-layer boundary layer mesh, which can more accurately capture the details of velocity changes at the wall, thereby improving the accuracy of the model. The inlet of the model is the velocity inlet, and the outlet is the pressure outlet. The coupled algorithm is chosen as the solution method. Under these conditions, the model converges quickly and the calculation accuracy is high. The results show that the resistance loss along the pipeline decreases as a power function with the increase of pipeline diameter, and there is a polynomial relationship between the pipeline flow and the resistance loss along the pipeline, while the mass concentration of fly ash slurry changes linearly with the resistance loss along the pipeline. In addition, three friction coefficient models, namely Blasius formula, Colebrook–White equation, and Wilson–Thomas model, were selected according to the flow characteristics of fly ash slurry. Based on the Blasius formula with the smallest relative calculation error, the Blasius formula was modified by multiple linear regression analysis to improve the accuracy of the frictional resistance coefficient model and to provide help for the design and use of separate layer grouting conveying system.